Systemic delivery of IL-27 by an adeno-associated viral vector inhibits T cell-mediated colitis and induces multiple inhibitory pathways in T cells. Issue 2 (22nd April 2016) - Zhu, Xiaotong; Liu, Zhihao; Liu, Jin-Qing; Zhu, Jianmin; Zhang, Jianchao; Davis, Jonathan P; Chu, Jianhong; Yu, Jianhua; Zhou, Jie; Li, Ming-Song; Bai, Xue-Feng
Abstract : Administration of AAV-IL-27 blocks autoimmune colitis via novel mechanisms. Abstract: IL-27 is a heterodimeric cytokine that is composed of two subunits, i.e., EBV-induced gene 3 and IL-27p28 (also known as IL-30). Although the role of endogenous IL-27 in the pathogenesis of autoimmune colitis, an experimental model of human inflammatory bowel disease, remains controversial, IL-27 local delivery has been shown to inhibit autoimmune colitis. IL-30 has been shown to inhibit Th1 and Th17 responses and is considered a potential therapeutic for certain autoimmune diseases. In this study, we have compared the therapeutic efficacy of adeno-associated viral vector-delivered IL-27 and IL-30 in a murine model of autoimmune colitis. We found that 1 single administration of adeno-associated viral vector-delivered IL-27, but not adeno-associated viral vector-delivered IL-30, nearly completely inhibited autoimmune colitis. Adeno-associated viral vector-delivered IL-27 administration inhibited Th17 responses and induced T cell expression of IL-10, programmed death ligand 1, and stem cell antigen 1. Intriguingly, adeno-associated viral vector-delivered IL-27 treatment enhanced Th1 responses and inhibited regulatory T cell responses. Experiments involving the adoptive transfer of IL-10-deficient T cells revealed that adeno-associated viral vector-delivered IL-27-induced IL-10 production was insufficient to mediate inhibition of autoimmune colitis, whereas anti-programmed death 1 antibody treatment resulted in the breaking of adeno-associated viral vector-delivered IL-27-induced T cell tolerance. Thus, systemic delivery of IL-27 inhibits Th17 responses and induces multiple inhibitory pathways, including programmed death ligand 1 in T cells, and adeno-associated viral vector-delivered IL-27, but not IL-30, may have a therapeutic potential for the treatment of human inflammatory bowel disease.